2022
DOI: 10.1096/fj.202200788r
|View full text |Cite
|
Sign up to set email alerts
|

Pore formation‐independent cell death induced by a β‐barrel pore‐forming toxin

Abstract: Vibrio cholerae cytolysin (VCC) is a βbarrel pore-forming toxin (β-PFT). It exhibits potent hemolytic activity against erythrocytes that appears to be a direct outcome of its pore-forming functionality. However, VCC-mediated cell-killing mechanism is more complicated in the case of nucleated mammalian cells. It How to cite this article: Kaur D, Verma P, Singh M, et al. Pore formation-independent cell death induced by a β-barrel pore-forming toxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Bacterial virulence factors, including a number of PFTs, are known to translocate to the mitochondria of the target cells and cause mitochondrial damage/dysfunction (Bielaszewska et al, 2013; Braun et al, 2007; Galmiche & Rassow, 2010; Genestier et al, 2005; Gupta et al, 2015; Kaur et al, 2022; Muller et al, 2002). Therefore, to elucidate the mechanistic basis of TDH‐mediated mitochondrial damage and cell death induction, we explored whether TDH could translocate to the mitochondria of the Caco‐2 and THP‐1 cells (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bacterial virulence factors, including a number of PFTs, are known to translocate to the mitochondria of the target cells and cause mitochondrial damage/dysfunction (Bielaszewska et al, 2013; Braun et al, 2007; Galmiche & Rassow, 2010; Genestier et al, 2005; Gupta et al, 2015; Kaur et al, 2022; Muller et al, 2002). Therefore, to elucidate the mechanistic basis of TDH‐mediated mitochondrial damage and cell death induction, we explored whether TDH could translocate to the mitochondria of the Caco‐2 and THP‐1 cells (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Staphylococcus aureus Panton‐Valentine leukocidin (PVL) has also been found to localize in the target cell mitochondria towards subsequent induction of mitochondrial damage and apoptotic cell death (Genestier et al, 2005). In a more recent study, Vibrio cholerae cytolysin (VCC) has been shown to be translocated into the mitochondria of the target cells and induce pore formation‐independent cell death (Kaur et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations